Draping for apparel design - Joseph-Armstrong, Helen; Ashdown, S. P. (Susan P.) (Fairchild Books, 2022)
"Draping for Apparel Design, Fourth Edition is the fully updated and revised edition of the seminal book pioneered by fashion education luminary Helen Joseph-Armstrong. This comprehensive guide provides step-by-step instruction for the beginning patternmaker and advanced techniques for the more experienced. Maintaining the vast array of examples and the book's easy-to-read style, revising author Susan Ashdown reflects current industry standards, both metric and imperial measurements, new sizing guides for diverse body types, and incorporates half-scale forms. New material on jackets, coats, and loose fitted knitwear add to this book's breadth of knowledge"--